Method the madness: Working towards a viable 'paradigm' for better understanding and supporting the athlete pathway - Weissensteiner, J. R. (Routledge handbook of talent identification and development in sport, 2017)
The developmental journey of an athlete from their `grass-roots` to international podium, is a long and at times, arduous one. The quest to find the right `road map` (i.e., developmental framework or model) that adequately captures the nuances of this experience, that can effectively navigate this journey for both the ahlete in question and that can guide and coordinate all key stakeholders invested in supporting the `athlete`, continues. Despite a predominance of highly cited and popular concepts and frameworks within the contemporary literature, gaps persist in the athlete pathway and the aligned practice and support of athletes (Bergeron et al., 2015; Gulbin, Croser, Morley, & Weissensteiner, 2013a; Gulbin & Weissensteiner, 2013; Toohey et al., 2015; Weissensteiner & Medlicott, 2015). As depicted in Figure 10.1, within the foundational levels of the athlete pathway, marked declines in the fundamental movement skills (the building blocks for later sporting skill), muscular strength and neuromuscular fitness and coordination of youth participants is occurring in unison with a greater emphasis on earlier, structured sport formats and sports specialization to the detriment of deliberate play and diversified sports sampling (Bergeron et al., 2015; Cote, Lidor, & Hackfort, 2009; Hardy, King, Espinel, Cosgrove, & Bauman, 2010a; Hardy, King, Farrell, Macniven, & Howlett, 2010b; Hardy, Barnett, & Espinel, & Okely, 2013; Jayanthi, LaBella, Fischer, Pasulka, & Dugas, 2015; Lloyd et al., 2015a; Myer et al., 2015; Oakley & Booth, 2004; Telford et al., 2012; Tester, Ackland, & Houghton, 2014). A decline in these foundational competencies are contributing to unrealised talent potential through compromised sport-specific skill development, increased injury risk, burnout and dropout (Bergeron et al., 2015; Cote et al., 2009; Fraser-Thomas, Cote, & Deakin, 2008;Jayanthi et al., 2015; Myer et al., 2015). Questionable and short-sighted coaching and club practices prevail, underpinned by a lack of understanding regarding the holistic nature of athlete development, the impact of biological maturation on adolescent sporting development and performance and the importance of injury prevention (Bergeron et al., 2015; Emery, Thierry-Olivier, Whittaker, Nettel-Aguirre, & van Mechelen, 2015; Malina, Rogol, Cumming, Coelho-e-Silva, & Figueiredo, 2015).